Introducing The World of Language and Literature and Increasing Students' Interest in Reading in Lower Grades - Melinda Syahputri; Hardiyanti, Sella; Lubis, Renni Ramadhani (Journal of General Education Science, 2024)
This research aims to find alternative ways to introduce the world of language and literature and increase students' reading interest in lower grades. Language and literature learning have an interrelated relationship. Literature without language cannot exist. The special characteristic of literature lies in the use of aesthetic language. Text-based Indonesian language learning contains two interests, namely language and literature. At the practical level, various stages of building a context, forming a model, building a text together and building a text independently emerge. Overall, these stages are integrated into learning practices, thereby providing students with the opportunity to optimize their potential both as a group and individually. Efforts to increase efforts to introduce the world of language and literature and increase students' interest in reading in lower grades are a shared responsibility, between the students themselves, teachers and parents. However, the low interest in reading among students in elementary schools is one of the obstacles, the lack of desire and willingness of the students themselves, teachers also do not require students to read books during the lessons taught to students. In an effort to introduce the world of language and literature and increase students' interest in reading in lower grades, students should be given support so that interest in reading emerges from themselves and introduced to reading materials so that students get used to reading, hence the reading habits of students when they are in elementary school. will foster a high interest in reading until students grow up. This research was carried out by formulating a research problem, looking for references from relevant and similar journals to analyze the data, journals were collected by searching the internet via Google Chendikia and/or Google Scholar. The data obtained was analyzed and compared. This research method used a descriptive research type with a quantitative approach. From the results of the analysis, it can introduce the world of language and literature and increase students' reading interest in lower grades.